Molecular characterization of metronidazole resistant Bacteroides strains from Kuwait. (June 2021) - Baaity, Zain; Jamal, Wafaa; Rotimi, Vincent O.; Burián, Katalin; Leitsch, David; Somogyvári, Ferenc; Nagy, Elisabeth; Sóki, József
Abstract: Eleven metronidazole resistant Bacteroides and one newly classified Phocaeicola dorei strain from Kuwait were investigated for their resistance mechanisms and the emergence of their resistant plasmids. All but one strain harbored nimE genes on differently sized plasmids. Of the 11 nimE genes, 9 were preceded by full copies of the prototype IS Bf6 insertion sequence element, one carried a truncated IS Bf6 and one was activated by an additional copy of IS 612 B. Nucleotide sequencing results showed that the nimE IS Bf6 distances were constant and all five different plasmids shared a common region, suggesting that (i) the nimE -IS Bf6 configuration was inserted into an undisclosed common genetic element, (ii) over time, this common element was mutated by insertions and deletions, spreading the resultant plasmids. Of the 10 B. fragilis strains in this collection, 6 were also cfiA -positive, one with full imipenem resistance, indicating a tendency for multidrug resistance (MDR) among such isolates. The significant number of metronidazole resistant Bacteroides spp. and P. dorei strains with the MDR phenotype warns of difficulties in treatment and suggests promoting adherence to antibiotic stewardship recommendations in Kuwait. Highlights: The rate of metronidazole resistance among Bacteroides strains in Kuwait is high. The resistance mechanism is mainly via nimE -IS Bf6 pairs harbored on small plasmids. Though these plasmids are differently sized, they may have a common origin. These strains also display a tendency to be multidrug-resistant (MDR). The MDR is especially due to the high co-carriage rate of the cfiA gene.